Venezuela: the crisis of the socialist model - Kulumzhanova, A.M. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2021)
Historically, Venezuela was one of the dynamically developing countries in Latin America, a major producer and exporter of oil, but internal social conflicts distracted the efficiency of the oil and cement industries, ferrous metallurgy, and telecommunications. Since the beginning 2014, the country has been in a state of the socioeconomic and political crises, which resulted in a recession in the welfare of the country’s citizens, the level of unemployment, poverty and social inequality rose sharply, and reached phenomenal record of negative indicators. The unstable situation in the oil market, economic sanctions of the US exert great pressure on the country’s economy, creating obstacles to the restoration of the previous volumes of oil production, which was the main source of state budget.